KONSTRUKSI MAKNA PROFESIONALISME DOSEN MELALUI PRAKTIK EVALUASI PEMBELAJARAN BAHASA - Abdul Hamid; Muchlas Suseno; Samsi Setiadi (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2025)
Abstract: This study investigates how English language lecturers construct the meaning of professionalism through their assessment practices in higher education. Amid growing emphasis on standardized and technology-based evaluation systems, the role of assessment as a site of ethical decision-making and pedagogical reflection remains underexplored. Drawing from a descriptive qualitative design with an interpretive paradigm, the study involved in-depth interviews with five English lecturers from two universities in Indonesia, supported by documentation analysis and thematic coding. The findings reveal that assessment functions not only as a technical procedure but also as a medium through which lecturers express values such as fairness, empathy, and integrity. These values are negotiated within the tensions between institutional policy and personal ethical convictions. The study highlights how lecturers engage in ongoing reflection, balance objectivity with contextual judgment, and navigate evaluative dilemmas to sustain their professional identity. Assessment is thus understood as a dynamic and dialogical process that contributes to the construction of a humanistic and ethically grounded professionalism. This research contributes to the growing discourse on reflective assessment and provides implications for policy development, professional development programs, and institutional support mechanisms that promote meaningful and context-sensitive evaluation practices.